A 3D-Printed PLCL Scaffold Coated with Collagen Type I and Its Biocompatibility. (28th February 2018) - He, Yong; Liu, Wei; Guan, Lianxiong; Chen, Jielin; Duan, Li; Jia, Zhaofeng; Huang, Jianghong; Li, Wencui; Liu, Jianquan; Xiong, Jianyi; Liu, Lijun; Wang, Daping
Abstract : Scaffolds play an important role in tissue engineering and their structure and biocompatibility have great influence on cell behaviors. In this study, poly(l-lactide-co- ε -caprolactone) (PLCL) scaffolds were printed by a 3D printing technology, low-temperature deposition manufacturing (LDM), and then PLCL scaffolds were treated by alkali and coated with collagen type I (COLI). The scaffolds were characterized by scanning electron microscopy (SEM), porosity test, mechanical test, and infrared spectroscopy. The prepared PLCL and PLCL-COLI scaffolds had three-dimensional (3D) porous structure and they not only have macropores but also have micropores in the deposited lines. Although the mechanical property of PLCL-COLI was slightly lower than that of PLCL scaffold, the hydrophilicity of PLCL-COLI was significantly enhanced. Rabbit articular chondrocytes were extracted and were identified as chondrocytes by toluidine blue staining. To study the biocompatibility, the chondrocytes were seeded on scaffolds for 1, 3, 5, 7, and 10 days. MTT assay showed that the proliferation of chondrocytes on PLCL-COLI scaffold was better than that on PLCL scaffold. And the morphology of cells on PLCL-COLI after 1-day culture was much better than that on PLCL. This 3D-printed PLCL scaffold coated with COLI shows a great potential application in tissue engineering.